2007
DOI: 10.1111/j.1399-3062.2006.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo monitoring of human cytomegalovirus‐specific CD8+ T‐cell responses using QuantiFERON®‐CMV

Abstract: We have developed a novel diagnostic technology to monitor the human cytomegalovirus (HCMV)-specific CD8+ T-cell responses that is based on the detection of secreted interferon-gamma (IFN-gamma) in the whole blood (referred to as QuantiFERON -CMV). Evaluation of QuantiFERON -CMV in healthy individuals revealed that this technology was at least as sensitive and with some HCMV epitopes more sensitive than the ELISPOT for detecting ex vivo IFN-gamma. Results from QuantiFERON -CMV assays showed 97% (36/37 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
146
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(153 citation statements)
references
References 24 publications
2
146
2
1
Order By: Relevance
“…These conclusions are strongly sup- ported by previous studies of other viral infections which have shown that the breadth of the cytotoxic T-lymphocyte response may be important in preventing viral pathogenesis (1,18). Another important implication of this study relates to the potential use of T-cell functional analysis as a diagnostic tool for identifying the levels of virus-specific T-cell responses which would predict the increased or decreased risk of symptomatic HCMV recrudescence (6,7,19). The diagnostic application of this technology will require an extended analysis of a larger cohort of transplant patients in various clinical settings to determine if the protection from HCMV disease in transplant patients is dependent on T-cell responses directed against a broad range of antigens rather than any single antigen.…”
mentioning
confidence: 59%
“…These conclusions are strongly sup- ported by previous studies of other viral infections which have shown that the breadth of the cytotoxic T-lymphocyte response may be important in preventing viral pathogenesis (1,18). Another important implication of this study relates to the potential use of T-cell functional analysis as a diagnostic tool for identifying the levels of virus-specific T-cell responses which would predict the increased or decreased risk of symptomatic HCMV recrudescence (6,7,19). The diagnostic application of this technology will require an extended analysis of a larger cohort of transplant patients in various clinical settings to determine if the protection from HCMV disease in transplant patients is dependent on T-cell responses directed against a broad range of antigens rather than any single antigen.…”
mentioning
confidence: 59%
“…Both the CMV ELISPOT and CMV-QuantiFERON assays detect IFN-␥ produced by antigen-stimulated peripheral blood mononuclear cells (PBMCs). The main differences between the assays include the antigen stimulus composition, with stimulation of CD8 ϩ T-cell responses in the CMV QuantiFERON assay (21) and stimulation of both CD4 ϩ and CD8 ϩ T-cell responses in the CMV ELISPOT assay (22,23). Moreover, the CMV QuantiFERON assay detects IFN-␥ in a volume of ϳ1 ml of whole blood, while the CMV ELISPOT assay detects IFN-␥ secreted by ϳ2 ϫ 10 5 PBMCs (22,23).…”
mentioning
confidence: 99%
“…In this study, two interferon gamma (IFN-␥) release assays (IGRA), the CMV enzyme-linked immunosorbent spot (ELISPOT) and CMV QuantiFERON assays, widely used to detect pathogenspecific CMI (15)(16)(17)(18)(19)(20)(21), were compared in a group of primarily and nonprimarily CMV-infected pregnant women and in a control group of healthy seropositive and seronegative pregnant and nonpregnant women without evidence of active CMV infection. Several characteristics differ between the CMV ELISPOT and CMV QuantiFERON assays.…”
mentioning
confidence: 99%